Polyhydroxylated sterols from the soft coral sarcophyton pauciplicatum - Tung, Pham The; Ngoc, Ninh Thi; Thao, Nguyen Phuong; Huong, Tran Thu; Thung, Do Cong; Thanh, Nguyen Van; Nam, Nguyen Hoai; Cuong, Nguyen Xuan; Kim, Young Ho; Kiem, Phan Van; Minh, Chau Van (Vietnam Journal of Chemistry, 2015)
The methanol extract of the soft coral Sarcophyton pauciplicatum afforded four sterols as (24S)-ergostane-3β,5α,6β,25-tetraol 25-monoacetate (1), (24S)-ergostane-3β,5α,6β,25-tetraol (2), (24S)-ergostane-1β,3β,5α,6β,25-pentaol 25-monoacetate (3), and (24S)-ergost-25-ene-1β,3β,5α,6β-tetraol (4) after subjecting it to various chromatographic experiments. The structures of isolated compounds were elucidated by 1D and 2D-NMR experiments and comparison of their NMR data with reported values. This is the first report of these compounds from                       S. pauciplicatum.